Analysis of the impact of measurement on the impedance stability of HVDC grids - Zhao, Dawei; Chen, Zaiyu; Bu, Jing; Li, Qun; Li, Qiang; Rong, Xiaohu (Frontiers in Energy Research, 2024)
The rapid advancement of power electronics technology has led to the development of more flexible DC transmission systems, revealing the issue of oscillations. In this paper, a novel impedance modeling approach for the DC side of Modular Multilevel Converters (MMCs) has been introduced to overcome the limitations of previous methods, which did not take into account the complete control structure and internal harmonic characteristics. An accurate impedance model has been established, integrating the types of disturbance signal sources used in impedance measurement and the impact of measurement device characteristics on model accuracy. This approach enhances the precision of impedance stability analysis, which is crucial for system stability. The model's effectiveness has been validated through simulations, demonstrating the influence of disturbance signal types and measurement device characteristics on the impedance stability of the MMC's DC side.